Characterization of Ty21a immunostimulatory effects in the mouse bladder - Polak, Lenka; Hojeij, Rim; Cesson, Valerie; Haefliger, Jacques-Antoine; Roger, Thierry; Lucca, Ilaria; Derré, Laurent; Nardelli-Haefliger, Denise; Domingos-Pereira, Sonia (Frontiers in Immunology, 2025)
Intravesical treatment with Salmonella enterica Ty21a, an oral typhoid-fever vaccine, has shown therapeutic potential against bladder tumors mainly through local immune-cell recruitment, particularly CD8+ T-cells. However, the mechanisms underlying its efficacy and the impact of bacterial formulation remain unclear. Here, we show that increased immune-cell infiltration was neither associated with modification in blood vessel density nor the generation of high endothelial venules, but rather with a transient increase in local vessel permeability, requiring live bacteria. Giving prior evidence that freshly harvested bacteria (Ty21aFR) were more efficient than lyophilized bacteria (Ty21aLYO), we tested both formulations intravesically in mice. Although, both similarly increased vascular permeability, Ty21aFR induced significantly greater immune-cell recruitment locally and more effective tumor regression in the orthotopic MB49 bladder cancer model. Chemokine analysis showed higher levels of C5a, CXCL2 and CXCL5 in Ty21aFR-treated bladders, however their receptors (C5aR, CXCR2) were barely detected on infiltrating T cells, precluding their direct involvement in T-cell recruitment. Instead, Ty21aFR increased C5aR+ and C5aR-CD11bhigh myeloid cells, suggesting their indirect influence on T-cell recruitment. We hypothesized that LPS, a TLR4 agonist, from Salmonella, might be involved. Indeed, CD8+ T-cell infiltration following Ty21aFR was significantly decreased in TLR4- and MyD88-KO mice. In contrast, myeloid-cell recruitment was only reduced in MyD88-KO mice, suggesting the involvement of TLR4-independent pathways in that process. This study is the first to identify Ty21a formulation-driven immunostimulatory differences in bladder cancer. Altogether, our data provide new insights into Ty21a’s immunostimulatory mechanisms and highlight the importance of bacterial formulation for optimizing bladder cancer treatment.